The development of energy-efficient vehicle using natural gas technologies (NGV) - Wan Amalin Suraya, Wan Arifin (2018)
Air pollution generally comes from emission of mobile and non-mobile sources. Pollution from mobile sources, such as vehicle is dominant in city centers throughout Malaysia. Natural gas is acknowledged as being mainstream alternative fuel. In Malaysia, pollution is not the only reason natural gas-powered vehicle were being introduced but also due to economic factor. Malaysia have massive, under exploited natural gas reserve. Natural gas reserve is actually four times larger than oil reserve. By using this natural resources, global warming and continuing oil price increases will no longer being an issue. The crisis is no longer a threat to other activities around the world, especially when using the alternative fuels with pollution-free nature. Malaysia can be considered as a fortunate country to have such an alternative fuel such as natural gas. Natural gas utilization benefits a lot greenhouse gaseous (GHG) reduction and other environment issues. As for a long-term development, the government incentives are becoming increasingly attractive. This project research aims to propose an installation of a NGV system on a 1.6 (A) Proton Waja CAMPRO car with an improvement on the bracket of compressed natural gas (CNG) tank and installation of gas leakage sensor to increase safety. The methodology started with designing on the bracket of CNG tank for enhancement and electrical circuit for the sensor to install in the NGV system. After that, fabricating on the bracket of the tank will be done. Next, the amount of gas emission from NGV car before and after install NGV system were determined by testing and commissioning on the car. In term of economic viability, cost saving after the installation is determined while for environment impact, the total emission reduction is calculated. An evaluation for the installation of the NGV system is made with intention to enhance Universiti Malaysia Pahang (UMP) image towards sustainability. This study and the project implementation based on this study hopefully will push the sustainable image of UMP to another level by a commitment of using natural resources with initiative to reduce carbon emission into the atmosphere.